Body mass index is negatively associated with telomere length: a collaborative cross-sectional meta-analysis of 87 observational studies. Issue 3 (11th September 2018) - Gielen, Marij; Hageman, Geja J; Antoniou, Evangelia E; Nordfjall, Katarina; Mangino, Massimo; Balasubramanyam, Muthuswamy; de Meyer, Tim; Hendricks, Audrey E; Giltay, Erik J; Hunt, Steven C; Nettleton, Jennifer A; Salpea, Klelia D; et al.
ABSTRACT: Background: Even before the onset of age-related diseases, obesity might be a contributing factor to the cumulative burden of oxidative stress and chronic inflammation throughout the life course. Obesity may therefore contribute to accelerated shortening of telomeres. Consequently, obese persons are more likely to have shorter telomeres, but the association between body mass index (BMI) and leukocyte telomere length (TL) might differ across the life span and between ethnicities and sexes. Objective: A collaborative cross-sectional meta-analysis of observational studies was conducted to investigate the associations between BMI and TL across the life span. Design: Eighty-seven distinct study samples were included in the meta-analysis capturing data from 146, 114 individuals. Study-specific age- and sex-adjusted regression coefficients were combined by using a random-effects model in which absolute [base pairs (bp)] and relative telomere to single-copy gene ratio (T/S ratio) TLs were regressed against BMI. Stratified analysis was performed by 3 age categories ("young": 18–60 y; "middle": 61–75 y; and "old": >75 y), sex, and ethnicity. Results: Each unit increase in BMI corresponded to a −3.99 bp (95% CI: −5.17, −2.81 bp) difference in TL in the total pooled sample; among young adults, each unit increase in BMI corresponded to a −7.67 bp (95% CI: −10.03, −5.31 bp) difference. Each unit increase in BMI corresponded to a −1.58 × 10 −3 unit T/S ratio (0.16% decrease; 95% CI: −2.14 × 10 −3, −1.01 × 10 −3 ) difference in age- and sex-adjusted relative TL in the total pooled sample; among young adults, each unit increase in BMI corresponded to a −2.58 × 10 −3 unit T/S ratio (0.26% decrease; 95% CI: −3.92 × 10 −3, −1.25 × 10 −3 ). The associations were predominantly for the white pooled population. No sex differences were observed. Conclusions: A higher BMI is associated with shorter telomeres, especially in younger individuals. The presently observed difference is not negligible. Meta-analyses of longitudinal studies evaluating change in body weight alongside change in TL are warranted.